Implementasi Desentralisasi Fiskal dalam Kebijakan Transfer Dana ke Daerah Pada Realisasi Anggaran Pendapatan dan Belanja Negara Tahun 2021 - Diah Riski Hardiana (Jurnal Administrasi dan Kebijakan Publik, 2023)
Fiscal decentralization has been officially implemented in Indonesia since the beginning of the reform, to be precise since January 2001, and implemented to create regional self-reliance. With the regional autonomy policy and fiscal decentralization, every region in Indonesia receives a large delegation of authority. In 2020, the Covid-19 Pandemic rocked the Indonesian economy. Economic growth continued to decline and had a negative impact on the people's economy, in addition to influencing the Transfer to Regions and Village Fund (TKDD) policies. Regional Governments are given the authority to prioritize the use of budget allocations for specific programs (refocusing), change allocations, and use the Regional Revenue and Expenditure Budget (APBD). Merilee S. Grindle's theory of implementation is the rationale for this research, focusing on aspects of the desired degree of change, location of decision-making, program implementation, and level of compliance and responsiveness. Regarding the desired degree of change, regional governments must reallocate budgets and refocus programs according to the central government's regulations. Aspects of program implementation, budget reallocation, and refocusing programs in several regions were successfully carried out. Aspects of the location of decision-making appropriate policies by prioritizing the health, social, economic, and regional financial sectors. While the aspects of compliance and responsiveness show that the policy has yet to be realized optimally, several problems were found in its implementation.